Interpolação das curvas de nível no programa Surfer 8.0 através de imagens do Google Earth | Interpolation of level curves in the Surfer 8.0 program through Google Earth images - Machado, José (Revista Geama, 2016)
RESUMO: O relevo é representado por diversas formas, dentre elas as curvas de nível (CN). Para obtenção das CN é necessário a interpolação dos pontos cotados. A utilização das CN, superfícies em 3D e modelos numéricos do terreno em programas computacionais avançam rapidamente e podem gerar alguns problemas. Esse trabalho compara os diferentes métodos de interpolação CN gerados pelo programa Surfer com os valores gráficos das imagens do Google Earth Pro. Foram utilizadas 12 interpolações disponíveis (Data Metrics, Inverse Distance, Kriging, Local Polynomial, Minimum Curvature, Modified Shepard Method, Moving Average, Natural Neighbor, Nearest Neighbor, Polynomial Regression, Radial Fuction e Triangulation with Linear Interpolation) para os dois tipos de terreno: plano e acidentado nas cidades de Torrão e Pampilhosa da Serra em Portugal. Foi gerado os gráficos de representação do relevo através da superfície 3D e CN. Foram atribuídos os conceitos excelente, ótima, boa, média e ruim representação do relevo e discutidos de acordo as representações do relevo com as imagens do Google Earth. Data Metrics, Polynomial Regression, Moving Average e Local Polynomial (ruim); Moving Average e Modified Shepard Method (regular); Nearest Neighbor (média); Inverse Distance (boa); Kriging e Radial Function (ótima) e Triangulation With Linear Interpolation e Natural Neighbor (Excelentes) condições de representação aos dados apresentados. Palavras-chave: Altimetria, representação do relevo, superfície 3D. ABSTRACT: The relief is represented by various forms, THEY among Contour (CN). To obtain the CN And Necessary interpolates the points listed. The use of the CN, 3D surface and Numerical Models do LAND IN Computer Programs are moving fast and CAN Generate Some Problems. This work compares the different interpolation methods CN generated hair Surfer program with OS Values charts of Google Earth Pro Pictures. Were used 12 interpolations available (data metrics, Inverse Distance, kriging, polynomial local minimum curvature, modified method Shepard, average mobile, Natural neighbor, nearest neighbor, polynomial regression, Radial fuction and Triangulation with Linear Interpolation) Pará The Two Types of Terrain: flat and hilly NAS Cities Lump and Pampilhosa da Serra in Portugal. Generated WAS THE Relief Representation through 3D graphics and CN surface. Were assigned OS Concepts excellent, good, Media & Poor Representation make raised and discussed in the Agreement as representations do with relief as Google Earth Images. Data Metrics, Polynomial Regression, Moving Average e Local Polynomial (bad); Moving Average e Modified Shepard Method (regular); Nearest Neighbor (media); Inverse Distance (good); Kriging e Radial Function (great) e Triangulation With Linear Interpolation e Natural Neighbor (excellent) conditions to representation presented dates. Keywords: Altimetry, relief representation, 3D surface.